Applying the Multi-Attribute Utility Theory (MAUT) to Accurately Determine Stunting Susceptibility Levels in Toddlers - Idris, Nur Oktavin; Umasugi, Nurain (Politeknik Negeri Batam, 2024)
Stunting is a condition of impaired growth and development in toddlers due to prolonged nutritional deprivation. In the Kota Timur Community Health Center, stunting is traditionally assessed based solely on body weight and height, neglecting other crucial factors such as socioeconomic status, maternal nutrition during pregnancy, history of illness, and dietary intake. This limited approach leads to inaccurate decision-making and misdiagnoses of stunting. This research applied the Multi-Attribute Utility Theory (MAUT) to identify stunting susceptibility levels in toddlers by integrating various determinants, including body weight, height, socioeconomic conditions, maternal nutrition during pregnancy, morbidity, and dietary intake. MAUT effectively integrates multiple criteria and manages data uncertainties through its utility concept, allowing for comparison across different alternatives to facilitate accurate decision-making. The results showed that Arbi, Manaf, and Aisyah were susceptible to stunting, with evaluation scores of 0.028, 0.288, and 0.299, respectively, while Daffa and Zayyan were not susceptible, with scores of 0.900 and 0.966, respectively. Therefore, the system utilizing MAUT to determine stunting susceptibility levels in toddlers can be adopted by health workers at the Kota Timur Community Health Center to enable efficient, quick, and accurate diagnosis by integrating multiple determinants of stunting susceptibility.